Body composition changes during 8 weeks of military training are not accurately captured by circumference-based assessments - Foulis, Stephen A.; Friedl, Karl E.; Spiering, Barry A.; Walker, Leila A.; Guerriere, Katelyn I.; Pecorelli, Vincent P.; Zeppetelli, David J.; Reynoso, Marinaliz C.; Taylor, Kathryn M.; Hughes, Julie M. (Frontiers in Physiology, 2023)
In 1981, the US military adopted body fat standards to promote physical readiness and prevent obesity. Separate circumference-based equations were developed for women and men. Both predictive equations were known to underestimate %BF. However, it was not known how well these abdominal circumference-based methods tracked changes in %BF. This study examined the validity of the circumference-based %BF equations for assessing changes in %BF in young adult recruits during Army Basic Combat Training (BCT). Dual-energy X-ray absorptiometry (DXA) and circumference-based measures of %BF were obtained in women (n = 481) and men (n = 926) at the start (pre-BCT) and end (post-BCT) of 8 weeks of BCT. Repeated-measure ANOVAs were used to assess differences between DXA and circumference pre-BCT and for the change during BCT. Pre-BCT, circumferences underestimated %BF relative to DXA, with mean errors of −6.0% ± 4.4% for women and −6.0% ± 3.5% for men (both p < 0.01), and no difference between sexes was observed (p = 0.77). DXA detected a −4.0% ± 2.4% and −3.3% ± 2.8% change in %BF for women and men in response to BCT, respectively (both p < 0.01), whereas circumference estimates of %BF indicated a 0.0% ± 3.3% (p = 0.86) change in women and a −2.2% ± 3.3% (p < 0.01) change in men (sex difference by technique p < 0.01). In conclusion, circumference-based measures underestimated %BF at the start of BCT in both sexes as compared to DXA. Circumference measures underestimated changes in %BF during BCT in men and did not detect changes in women. These findings suggest that circumference-based %BF metrics may not be an appropriate tool to track changes in body composition during short duration training.